MicroRNA-28-5p Regulates Liver Cancer Stem Cell Expansion via IGF-1 Pathway - Qing Xia; Tao Han; Pinghua Yang; Ruoyu Wang; Hengyu Li; Jin Zhang; Xinfeng Zhou (Stem Cells International)
Background. MicroRNAs (miRNAs) play a critical role in the regulation of cancer stem cells (CSCs). However, the role of miRNAs in liver CSCs has not been fully elucidated. Methods. Real-time PCR was used to detect the expression of miR-miR-28-5p in liver cancer stem cells (CSCs). The impact of miR-28-5p on liver CSC expansion was investigated both in vivo and in vitro. The correlation between miR-28-5p expression and sorafenib benefits in HCC was further evaluated in patient-derived xenografts (PDXs). Results. Our data showed that miR-28-5p was downregulated in sorted EpCAM- and CD24-positive liver CSCs. Biofunctional investigations revealed that knockdown miR-28-5p promoted liver CSC self-renewal and tumorigenesis. Consistently, miR-28-5p overexpression inhibited liver CSC’s self-renewal and tumorigenesis. Mechanistically, we found that insulin-like growth factor-1 (IGF-1) was a direct target of miR-28-5p in liver CSCs, and the effects of miR-28-5p on liver CSC’s self-renewal and tumorigenesis were dependent on IGF-1. The correlation between miR-28-5p and IGF-1 was confirmed in human HCC tissues. Furthermore, the miR-28-5p knockdown HCC cells were more sensitive to sorafenib treatment. Analysis of patient-derived xenografts (PDXs) further demonstrated that the miR-28-5p may predict sorafenib benefits in HCC patients. Conclusion. Our findings revealed the crucial role of the miR-28-5p in liver CSC expansion and sorafenib response, rendering miR-28-5p an optimal therapeutic target for HCC.